Intravenous Home Inotropic Use Is Safe in Pediatric Patients Awaiting Transplantation. (January 2015) - Birnbaum, Brian F.; Simpson, Kathleen E.; Boschert, Traci A.; Zheng, Jie; Wallendorf, Michael J.; Schechtman, Kenneth; Canter, Charles E.
<x xml:space="preserve">Abstract</x> Background— Intravenous inotropic therapy can be used to support children awaiting heart transplantation. Although use of this therapy is discouraged in adults because of poor outcomes, its use in children, particularly outpatient, has had limited evaluation. We aimed to evaluate the safety and efficacy of this practice. Methods and Results— A retrospective analysis of an intent to treat protocol was completed on United Network for Organ Sharing status 1A patients discharged on inotropic therapy from 1999 until 2012. Intravenous inotropic therapy was initiated for cardiac symptoms not amenable to oral therapy. Patients who were not status 1A or required >1 inotrope were excluded. Efficacy was analyzed by time to first event: transplantation; readmission until transplantation; improvement leading to inotrope withdrawal; or death. Safety included analysis of infection rates, line malfunctions, temporary hospitalization, neurological events, and arrhythmias. One hundred six patients met inclusion criteria. The mean age was 10.1±6.4 years, 47% of patients had congenital heart disease, and 80% of these patients had single ventricle physiology. In patients without congenital heart disease, 53% had dilated cardiomyopathy, 91% of patients received milrinone, 85% of patients underwent transplantation, 8% of patients successfully weaned from support as outpatients, whereas 6% died. Fifty percent of patients were readmitted before transplantation or weaning from support, of which 64% required only 1 readmission. The majority of readmissions were for heart failure. Conclusions— Outpatient intravenous inotropic therapy can be safely used as a bridge to transplantation in pediatric patients. A minority of patients can discontinue inotropic therapy because of clinical improvement.